Physicochemical Characterization of Star Anise Silver Nanoparticles Incorporated Chitosan Biomaterial for Absorb Water and Cure Wounds - M. Prabhahar; Gomathi Kannayiram; S. Prakash; M. Saravanakumar; Sangeetha Krishnamoorthi; S. Sendilvelan; P. Rahul Senthan; T. S. Ashikmon; M. Karthik; Haiter Lenin (Adsorption Science & Technology)
Chronic wounds threaten the geriatric society worldwide irrespective of their social status. The current treatment approach to cure chronic ailments is associated with its demerits. A novel treatment approach that is coordinated is required to adsorb water from wounds and cure chronic wounds. Star anise condiment used in the Indian kitchen is shown to have the potency to cure various ailments. In this study, silver nanoparticles were prepared using the star anise extract. The biological potency of star anise extract was confirmed through Gas Chromatography Mass Spectroscopy, antioxidant assay, and anti-inflammatory study. From the DPPH assay result, it was inferred that star anise extract was able to scavenge the free radicals at the concentration of 10 μg/ml using the aqueous extract silver nanoparticles were prepared. The prepared particles were characterized by UV-visible, scanning electron microscopy, and their biological efficacy was determined for their potency against bacteria and prevention of protein aggregation. The anti-inflammatory assay suggests that nanoparticles prevent the aggregation of proteins in a dose-dependent manner. IC50 was found to be 20 μg/ml. The synthesized nanoparticle was incorporated into the chitosan biomaterial and characterized by various physicochemical parameters such as differential scanning calorimetry, scanning electron microscopy, FTIR, and thermogravimetric analysis. According to the findings, silver nanoparticles incorporated in chitosan biomaterials can be used to adsorb water from wounds and wound healing materials.